Температурна залежність питомої електропровідності монокристалів Tl1-xIn1-xGexSe2 (x = 0,1; 0,2) уздовж і перпендикулярно до шарів - Кітик, Іван; Мирончук, Галина; Замуруєва, Оксана; Парасюк, Олег; Шаварова, Ганна; Kityk, Ivan; Mironchuk, Galyna; Zamurueva, Oksana; Parasyuk, Oleg; Shavarova, Anna (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Проаналізовано температурні залежності питомої електропровідності в монокристалах Tl1-xIn1-xGexSe2 уздовж та перпендикулярно до шарів. Показано, що в температурному інтервалі 100–300 K спостерігається провідність термозбуджених домішкових носіїв заряду по дозволеній зоні й стрибкова провідність за локалізованими станами. ; We analyzed the temperature dependence of conductivity in monocrystals Tl1-xIn1-xGexSe2 along and perpendicular to the layers. It is shown that in the temperature range 100 – 300 K the conductivity of thermal activated impurity carriers over the allowed band and hopping conductivity over localized states takes place. The activation energy of impurity conductivity is determined. The density of localized states near the Fermi level, the energy spread of these states and the average length of carrier hops at different temperatures is estimated.
The Тemperature Dependence of the Electrical Conductivity of Single Crystals Tl1-xIn1-xGaxSe2 (x = 0,1; 0,2) Along and Perpendicular to the Layers
Keywords: енергія активації; стрибкова провідність; густина локалізованих станів.; activation energy; hopping conductivity; density of localized states